Flora of high mountain tropical peatlands: threats and management measures, Talamanca Range, Costa Rica - González, Frank (2025)
Introduction: Tropical peatlands are highly fragile vegetal formations, especially vulnerable to anthropogenic impacts and changes in climatic conditions. Objective: To characterize the flora of the Talamanca peatlands, as well as identify their dynamics, threats, and impacts. Methods: The flora was analyzed in five peat bogs located in the Buenavista Massif, along the Inter-American Highway, at altitudes of 2 400 - 3 100 m, through field sampling. Subsequently, a Floristic Value Index (IVF) was designed to assess the state of conservation. Results: The floristic richness was determined in the peat bogs studied. A lower biological diversity was found in the three peatlands outside the state-protected natural spaces, suggesting the influence of the edge effect and agro-productive activities or their proximity to the Highway. In contrast, the Salsipuedes and Cerro Paramillo peatlands exhibited greater diversity, highlighting genera such as Blechnum, Puya, Chusquea, Myrsine and Vaccinium, in association with the bryophyte genus Sphagnum. A different floral composition was observed along the strip near the Inter-American Highway, characterized by species with lower water demand, especially genera such as Rubus and Pteridium, among others. Conclusion: From the identified floristic composition, the importance of peatlands as part of the mesoamerican hotspot ecosystems was determined, not only as repositories of biodiversity but also as sensitive indicators of human influence and environmental threats in the region associated with anthropic impact and climate change.